OUTCOME AND COMPLICATIONS OF ACUTE INTERMITTENT PERITONEAL DIALYSIS IN AL-KINDI TEACHING HOSPITAL (Iraqi Journal of Medical Sciences, 2016)
Background:Acute peritoneal dialysis is commonly practiced in IRAQ. Objective:To evaluate and improve the management of peritoneal dialysis in Al-Kindi Teaching Hospital.Methods: Six hundred and sixty nine patients underwent peritoneal dialysis during the period from January 2011 to June 2012. The mean age of patients was 54±13.9 years. Among the patients, there were 168 cases of acute renal failure, and 501 cases of chronic renal failure requiring acute dialysis.Results:Acute peritoneal dialysis performed on patients admitted in dialysis unit of Al-Kindi Teaching Hospital was safe, a simple procedure, easily tolerated by the patient and requiring less expertise than hemodialysis and had complication rates nearly comparable to other established centers.Complications occurred in 349 patients (52%). The most common complication was bleed¬ing in the peritoneal cavity (30%) while dialysis solution leak was the second most common complication (25%). Dialysis episodes complicated by peritonitis was (2.5%). Death rate was 15%.Conclusion:Acute peritoneal dialysis was performed safely and effectively in Al-Kindi Teaching Hospital. Improvements are possible through closer supervision of new doctors and tighter nursing precaution.Key Words:Acute peritoneal dialysis, outcome.
Keywords: Acute peritoneal dialysis; outcome